Habit and the Extended Mind: Fleshing Out the Extended Mind Theory with Merleau-Pontian Phenomenology - Richard Charles Strong (Rosenberg & Sellier, 2016)
This short essay attempts to flesh out the extended mind thesis by showing the nontrivial role of the body in skilled epistemic action. This is attempted by bringing Merleau-Ponty’s notion of the body schema together with Clark and Chalmers account of the extended mind. What the author hopes to show is that the incorporation of new habits into one’s body schema can make a meaningful difference for extended cognition as it regards behavioral competence, systemic performance, endorsement of external components, and typical invocation of external components. Habitualization of one’s body to environment and things in the environment is perhaps not a central part of the cognitive system - nor is it always necessary - but habit can and does make a meaningful difference in how well a coupled cognitive system might function and therefore ought to be taken into account. Moreover, habit highlights the extent to which enhanced cognitive performance relies on the body and its organs in conjunction with mind and thing. The essay proceeds by introducing Clark and Chalmers’ version of the extended mind hypothesis from before turning to Merleau-Ponty’s notion of the acquisition of habit qua modifications of the body-schema in conjunction with the extended mind.